TUTUR PUJIAN GURU DALAM INTERAKSI PEMBELAJARAN DI KELAS - Ahmad Fadilahtur Rahman (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This study aimed to describe the form and function apreciation speech act in the interaction in the classroom. This study used descriptive qualitative approach. From the research found a form of apreciation speech act in the learning interaction in the form of declarative sentences, sentence introgatif, and imperative sentences. While the function of speech act earned praise for smoothing function apreciation, smoothes warning, advise, and provide reinforcement.